Enjeux de la Tunisie orientale : un territoire développé et un environnement à protéger - Walid Chouari; Mongi Belarem (Confins)
Three decades in eastern Tunisia, the rise of environmental problems and natural hazards became apparent: erosion, pollution and hydrodynamic and hydrological risks...Without restatement of this trend, the country could enter a downward spiral; losing the assets that make wealth and abandoning a portion of its population live in an evil. These perspectives needed to initiate a global reflection on the Tunisian space, on its limitations and risks, and the strengths and means available to guide changes in the perspective of economic development that improves the quality of human life.